Generation of neural progenitor cells from porcine‐induced pluripotent stem cells. (23rd November 2020) - Machado, Lucas Simões; Pieri, Naira Caroline Godoy; Botigelli, Ramon Cesar; de Castro, Raquel Vasconcelos Guimarães; de Souza, Aline Fernanda; Bridi, Alessandra; Lima, Marina Amaro; Fantinato Neto, Paulo; Pessôa, Laís Vicari de Figueiredo; Martins, Simone Maria Massami Kitamura; De Andrade, André Furugen Cesar; Freude, Kristine Karla; et al.
Summary: In this study, porcine embryonic fibroblasts (pEFs) were reprogrammed into porcine‐induced pluripotent stem cells (piPSCs) using either human or mouse specific sequences for the OCT4, SOX2, c‐Myc, and KLF4 transcription factors. In total, three pEFs lines were reprogrammed, cultured for at least 15 passages, and characterized regarding their pluripotency status (alkaline phosphatase expression, embryoid body formation, expression of exogenous and endogenous genes, and immunofluorescence). Two piPSC lines were further differentiated, using chemical inhibitors, into putative neural progenitor‐like (NPC‐like) cells with subsequent analyses of their morphology and expression of neural markers such as NESTIN and GFAP as well as immunofluorescent labeling of NESTIN, β‐TUBULIN III, and VIMENTIN. NPC‐like cells were positive for all the neural markers tested. These results evidence of the generation of porcine NPC‐like cells after in vitro induction with chemical inhibitors, representing an adequate model for future regenerative and translational medicine research.